Peanut lipids influence the response of bronchial epithelial cells to the peanut allergens Ara h 1 and Ara h 2 by decreasing barrier permeability - Palladino, Chiara; Ellinger, Isabella; Kalic, Tanja; Humeniuk, Piotr; Ret, Davide; Mayr, Vanessa; Hafner, Christine; Hemmer, Wolfgang; Hoffmann-Sommergruber, Karin; Untersmayr, Eva; Bublin, Merima; Radauer, Christian; et al. (Frontiers in Molecular Biosciences, 2023)
Background: Peanut-allergic individuals react upon their first known ingestion of peanuts, suggesting sensitization occurs through non-oral exposure. Increasing evidence suggests that the respiratory tract is a probable site for sensitization to environmental peanuts. However, the response of the bronchial epithelium to peanut allergens has never been explored. Furthermore, food matrix-derived lipids play an important role in allergic sensitization. Objective: To contribute to a better understanding of the mechanisms of allergic sensitization to peanuts via inhalation, by exploring the direct effect of the major peanut allergens Ara h 1 and Ara h 2 and peanut lipids (PNL) on bronchial epithelial cells. Methods: Polarized monolayers of the bronchial epithelial cell line 16HBE14o- were stimulated apically with peanut allergens and/or PNL. Barrier integrity, transport of allergens across the monolayers, and release of mediators were monitored. Results: Ara h 1 and Ara h 2 impacted the barrier integrity of the 16HBE14o- bronchial epithelial cells and crossed the epithelial barrier. Ara h 1 also induced the release of pro-inflammatory mediators. PNL improved the barrier function of the cell monolayers, decreased paracellular permeability and reduced the amount of allergens crossing the epithelial layer. Conclusion: Our study provides evidence of the transport of Ara h 1 and Ara h 2 across the airway epithelium, of the induction of a pro-inflammatory milieu, and identifies an important role for PNL in controlling the amount of allergens that can cross the epithelial barrier. These, all together, contribute to a better understanding of the effects of peanuts exposure on the respiratory tract.